Les lexiques islamiques comme reflet de la société religieuse de la tribu Malinké en côte d'Ivoire : une étude sociolinguistique du roman Allah N'est Pas Obligé - Sepi Sepi; Bernadus Wahyudi Joko Santoso (Lingua Litteria Journal, 2026)
The use of special lexicon and language variation is one of the studies in the field of sociolinguistics. Hence, this study aimes to analyse the use of Islamic vocabulary by the Malinke people in the novel *Allah Is Not Obliged* illustrates the connection between language and the character of this community, while also describing their situation and environment. Lexical data was collected using listening and note-taking. Analysis of language use and recording of lexical forms present in the novel's narrative and dialogues yielded 30 Islamic lexical items, derived from variations of French and Malinke. Analysis of the results revealed a binary opposition in vocabulary use, between positive (religious) and negative (offensive) contexts. It was also observed that the chaotic context of the country influenced language use. In addition to uncovering the socio-cultural conditions of the Malinke people, this study also aims to present a thematic vocabulary in French related to Islam, for example the word "kesyahidan" in Indonesian translated as "martyr" in French.